Study the Effect of Alcoholic Extract of Nigella sativa Seeds on Trichomomas vaginalis In Vitro - Al-Ammash, Maroof Sabti Juma (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study included experimental effect of Metronidazole drug and Alcoholic extract of Nigella sativa seeds on T. vaginalis that cultivated on i i Results showed that the numbers of parasite began increasing during a period after 24-48 hrs then began decreasing after 72-96 hrs, so that 72 hrs from growth considered logarithmic phase of T. vaginalis growth. Present results showed poisonous effect of N. sativa alcoholic extract that was prepared in laboratory and imported at concentrations (450, 550, 650 and 750) mg/ml on T. vaginalis by observing gradual decrease of trophozoite numbers with concentrate increase of extracts during growth periods (24, 48, 72 and 96) hrs. Different concentrations of Metronidazole were used as chemical therapy and control model, the results of the drug effects were followed-up daily, where current results showed (after 24 hours of concentration added) a high reduction in number and activity of the parasites at all concentrations of the drug were , p ci lly 150 200 Î¼g/ l, th parasites disappeared completely after 96 hours, also the inhibitory concentration50 (IC50) of the parasit w 100 Î¼g/ l ( ft r 48 h r incubation). The inhibitory effect of N. sativa alcoholic extract on the number and activity of T. vaginalis parasite was noted that the concentrations (450 and 550 mg/ml) were approximated in their effect on parasite growth, while the concentrations 650 and 750 mg/ml were the best in their inhibitory activity for parasite growth after 96 hours of addition. The concentration that causes 50% of death inculture (IC50) was 550 mg/ml (after 72 hours of concentration addition).